« L’œil du hibou ». Le Flaubert au pluriel de Calvino - Susi Pietri (Flaubert: Revue Critique et Génétique)
Flaubert represents for Italo Calvino an absolute of formal invention that he interrogates (often mediated through other writers) according to three constellations of reading: the invisible, the unknowable, the unnameable. “Several Flaubert(s) in the plural” are thus inscribed throughout Calvino’s theoretical texts over time: nihilist Flaubert; supreme Model of work on form; Master of doubt and skepticism; critic of culture and of the plurality of languages; forerunner of the avant-gardes; paradigm of narrative visibility; invisible “God” of infinity at the heart of the infinitesimal; exemplary witness of the dissolution of knowledge; testamentary executor of the romance of convention; literary ancestor of “knowledge-as-multiplicity”; seeker of the absolute through the encounter with otherness.